(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: It derived from Latin word meaning nest of hair. The term pilonidel sinus describes a condition found in the natal cleft overlying the coccyx, consisting one or more usually, midline opening. It is chronic inflammatory condition usually affects the young adult. Objectives: To compare the outcomes between open and closed technique of surgical management of pilonidal sinus. Methods: A total 50 patients of pilonidal sinus were admitted. Details history, physical examination, and investigations like sinogram were done. The patients were divided into two groups like group A (open) group B (closed technique). Each group include 25 patients. Results: Wound infection was found in 4 (8%) patients in open technique managed with regular dressing and antibiotics. Complications were found in 10 cases in closed technique managed in closed dressing. Recurrence rate found in open technique 3 (6%) patients and closed technique 7 (14%) patients. Conclusion: From our experience, It is surgical challenge. Both technique is effective but open technique is better option as recurrence rate is low. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 51-52